Factors Influencing Psychological Well-being (PWB) in Students Participating in Merdeka Belajar Kampus Merdeka (MBKM) Program - Damayanti, Rika; Islamia, Intan; Agustriyani, Feri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This study aims to determine what factors can influence psychological well-being (PWB) in students participating in the MBKM program. The sample was selected using a quantitative cross-sectional study method with the criteria of active students and MBKM participants. A total of 83 students were involved in filling out the questionnaire in this study. The data collection technique in this study used six scales, including socio-economic status, religiosity, social support, healthy lifestyle, academic stress, university support, and PWB. The analysis techniques used in the study were descriptive statistical analysis and factor analysis with the help of SPSS software. The factor analysis results showed that three main factors influenced PWB in students, including religiosity, student social support, and healthy lifestyle. These findings indicate that in addition to academic factors, psychological and social factors also play an important role in supporting the psychological well-being of MBKM students. The implications of these findings can be used as a basis for developing more effective educational and support strategies for students to improve their psychological well-being.Keywords: psychological well-being, students, MBKM